Model Interaksi dan Resepsi Dosen Perguruan Tinggi Islam Terhadap Al-Qur'an - Naqiyah, Naqiyah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2020)
There are various kinds of interactions between people and the Qur’an in Muslim societies. Ideally, lecturers of Islamic universities have a quality interaction to the Qur’an. This paper aims at elaborating various models of interaction in behaving the Qur’an by the lecturers of IAIN Purwokerto. It explores the forms, values, motives and interpretations of lecturers’ interaction to the Qur’an. The research employs an integrative approach by combining social approach of David Murley’s reception theory on three possibilities for accepting text and religious approach on three levels of worshipers. The paper argues that the way the lecturers behave the Qur’an is classified into four receptive model of interaction: liturgical, aesthetic, intellectual, and mystical reception. The four model of interactions are mostly representing the ‘dominant reading,’ where they interact to the Qur’an as it was. While some others are typically representing the ‘negotiated reading’ and even ‘transactional,’ where they improve a new reading of the Qur’an which in line to their socio-cultural milieu.